Quantitative Analysis of Floristic Composition, Biological Spectrum and Leaf Spectrum of a Sacred Grove in Jhargram District, West Bengal, India - Uday Kumar Sen; Ram Kumar Bhakat (Biogenesis: Jurnal Ilmiah Biologi, 2020)
Sacred Groves are tracts of virgin forests, left untouched and protected by local people, because of culture and religious beliefs. These tracts are remnants of the once-dominant flora, reservoirs of the rich biodiversity, and the last refuge for preserving the rich indigenous culture and traditions. For these reasons, the biological and leaf spectra, as well as the conservation status of the current sacred grove vegetation, Maa Mongalmoyee Than (MMT) in Jhargram district of West Bengal, India, have been studied. Data were collected during different seasons. The floristic list is taxonomically arranged based on clade, order, and family. In addition, photographs of some common, locally uncommon, endemic and valuable plant species within the sacred grove were taken. The herbarium sheets were then described by matching properly annotated materials available at the Herbarium Section of Vidyasagar University as well as the Botanical Survey of India. The results of floristic studies showed 217 MMT's angiosperm species, belonging to 196 genera, distributed under 59 families of 27 orders. Furthermore, Poales (13.82%) and Fabaceae (12.44%) are the dominant order and family, respectively, in terms of species population. Meanwhile, the biological spectrum showed the grove enjoys a "thero-chamaephyte" phytoclimate form, as well as a comparatively undisturbed status, being a sacred grove. Also, the preservation of germplasm within the grove is based on traditional belief in the social system.